THE EARLIEST PRINTED COLLECTION OF PERSIAN PROVERBS - Shurgaia, Tea (Proverbium - Yearbook, 2012)
Some proverb bibliographies mention Proverbiorum Et Sententiarum Persicarvm Centuria, A Hundred Persian Proverbs and Aphorism, compiled by Levin Warner and published in 1644 in Leiden. No special review or almost no mention of this collection can be traced in scholarly literature concerning the recording of Persian proverbs. In my opinion, even though Warner’s collection is of more historical than paremiological value, it has unfortunately been largely forgotten. Levin Warner’s work should be considered as the first collection of translated Persian proverbs, rather than that of Thomas Roebuck published in Calcutta in 1824. It is worth noting that A Hundred Persian Proverbs and Aphorisms is the oldest printed collection of Persian proverbs.